Heart of the Nile [large type] - Thomas, Will, 1958- (Thomas, Will, 1958- Barker & Llewelyn novel, 2023)
"Cyrus Barker, along with his former assistant and now partner Thomas Llewelyn, is the premier enquiry agent in all of 19th century London, and beyond. They've thwarted the designs of villains and crooks of all sorts, helped Scotland Yard crack their most challenging cases, and worked for the Her Majesty's Government at the very highest levels. But nothing has been quite as challenging and dangerous as the latest case that comes to find them. In 1893, a volunteer at the British Museum makes a startling discovery. When examining a mummy in the museum's collection, he discovers there is a giant ruby in the shape of a heart buried in the chest of the mummy. Even more startling, the mummy might well be Cleopatra. The following morning, the volunteer is found floating in the Thames and the ruby has gone missing. Hired by the victim's wife to learn the truth behind his death, Barker and Llewelyn find themselves in the crosshairs -- now they must avoid a violent street gang, a ruthless collector, and the British Museum itself in order to find the killer and safeguard the gem."--